The Best Web-Based Employee Assessment Application Using the SAW Method - Chelsea Aprilia Tendean; Kristofel Santa; Efraim Ronald Stefanus Moningkey (Newinera Publisher, 2026)
This study aims to develop a web-based system to evaluate the performance of top employees at the Secretariat of the Minahasa Regency Regional People's Representative Council. Previously, the performance evaluation process was conducted manually, resulting in inefficiency in data management, low transparency, and subjectivity in decision-making. To address these issues, a decision support system was designed and implemented using the Simple Additive Weighting (SAW) method to calculate the final score for each employee based on predetermined performance criteria. This study employed a structured system development approach, which included the stages of needs analysis, system design, implementation, testing, and maintenance. The system was developed using a web-based programming environment supported by a relational database to manage employee data, assessment criteria, and evaluation results. Employee performance assessments were conducted based on several criteria, including discipline, attendance, responsibility, and productivity, each of which was weighted according to its level of importance. The system performed data normalization, weighting, and ranking to objectively determine the best-performing employees. Functional testing using the black box method showed that all system features, including user authentication, data processing, performance evaluation, and report generation, functioned as expected. The results of the study show that the developed system is able to increase efficiency, accuracy, and transparency in the employee performance assessment process, and can be used as a reliable decision-making tool for management in selecting high-performing employees and improving overall organizational performance.